Makespan algorithms and heuristic for internet-based collaborative manufacturing process using bottleneck approach - Bareduan, Sallehahmad; Hasan, Sulaiman (Scientific Research, 2010)
This paper presents makespan algorithms and scheduling heuristic for an Internet-based collaborative design and manufacturing process using bottleneck approach. The collaborative manufacturing process resembles a permutation re-entrant flow shop environment with four machines executing the process routing of M1,M2,M3,M4,M3,M4 in which the combination of the last three processes of M4,M3,M4 has high tendency of exhibiting dominant machine characteristic. It was shown that using bottleneck-based analysis, effective makespan algorithms and constructive heuristic can be developed to solve for near-optimal scheduling sequence. At strong machine dominance level and medium to large job numbers, this heuristic shows better makespan performance compared to the NEH.